Examining the Relationship Between the Level of Development of Countries and the Participation of Women in the Labor Market - Sümer Ertaş, İrem; Uzunöz, Meral (International Journal of Contemporary Economics and Administrative Sciences, 2023)
Regardless of the development level of the countries, the labor force participation rate plays a critical role in the social and economic development of the countries. For this reason, women's participation in the labor market, which creates half of the world's population, is very important in terms of improving the position of women in society and taking part in business life. It is evidence of gender inequality that women have less labor force participation than men or more barriers for women in the labor market. However, for the last 20 years, more studies have been carried out on women's participation in the workforce and ensuring gender equality, and projects that increase women's participation in the workforce have been supported. Social and economic development of countries accelerates as women take part in the labor market and work on equal terms with men in the labor market. In this study, it is aimed to examine the difference between men and women in the labor market and female employment in selected countries and regions using ILO, Word Bank and OECD data. It focuses on the difficulties experienced by women in the labor market and the barriers women face when entering the labor market. By emphasizing the importance of women's position in the economy, proposals, conventions and decisions prepared by international organizations in order to prevent gender inequality in the labor market for the social and economic development of countries and to prevent all kinds of violence and discrimination against women are examined. The aim of this study is to draw attention to the positive relationship between women's role in the labor market and economic and social development, and to offer solutions and policy recommendations to prevent gender inequalities in the labor market for the sustainable economic and social development of countries.